Hubungan Gaya Hidup dan Pola Makan dengan Kejadian Hipertensi di Desa Ngadirejo Temanggung Jawa Tengah 2025 - Adi Putra, Hodiri (Universitas Widya Mataram, 2025)
The achievement of hypertension case discovery in Ngadirejo Village in 2024 was 784. Based on information from the Head of Non-Communicable Disease Coordinator and the Head of Nutrition Coordinator of Ngadirejo Health Center, the main problems faced are poor diet and lifestyle. Objective: To determine the relationship between lifestyle and diet with the incidence of hypertension in Ngadirejo Village. Method: Quantitative research with a Case Control Survey approach. The study was conducted in Ngadirejo Village with a population of 26 people. The sampling technique used the Total sampling technique. The sample in the study amounted to 26 cases and 26 controls with a total of 52 respondents. This research instrument used a questionnaire and the results of the study were analyzed using the Chi Square test. Results: The results of the study were obtained in the lifestyle variable, there was a significant relationship between lifestyle and the incidence of hypertension with a p-value (0.013). And in the diet variable, there was a significant relationship between diet and the incidence of hypertension with a p-value (0.030). Conclusion: There is a relationship between lifestyle and diet with the incidence of hypertension in Ngadirejo Village, Ngadirejo District, Temanggung Regency, Central Java.